The impact of operational risk on credit risk and liquidity risk: Case of Tunisian banks (Journal of Academic Finance, 2020)
The purpose of this study is to verify if an interaction exists between operational risk and other financial risks. Interaction between operational risk and other risks pervades the whole range of adverse events that affect banking outcomes in the developing economies. The interaction sums up the real dynamics of operational risk in banking. Every threat that a bank faces crystallizes some operational risk somehow. In this way, an operational risk encapsulated in credit risk, the probability that counterparties may default on their bank loans. A similar interaction exists between operational risk and liquidity risk. We perform Granger-causality tests in a dynamic GMM panel estimator framework on an exhaustive data set of Tunisian banks, which mainly includes 10 listed banks from 1998 to 2016. We show that operational risk positively Granger-causes credit risk in these banks. However, the relationship between operational risk and liquidity risk was found to be insignificant.